Дослідження наукового потенціалу України: аналітичний огляд результатів конкурсу "молодий вчений року" - Леванда, О.; Маганова, Тамара Валеріївна; Levanda, О.; Mahanova, T. V. (My University, 2025)
У складних соціально-економічних умовах молоді наукові кадри є основним чинником збереження сьогоднішнього рівня функціонування економіки країни та її подальшого інноваційного розвитку. Останні негативні тенденції еміграції продуктивних сил, обмеження фінансування та наукової пасивності молоді свідчать про необхідність створення механізмів та інструментів збереження та примноження активів держави. Проте будь-яке управлінське рішення, зокрема пов’язане з формуванням політик стимулювання розвитку наукового потенціалу, неможливе без оцінки реального стану справ — аналізу кількісних та якісних характеристик наукових кадрів країни, оцінки її наукового потенціалу. Варіативність таких підходів значна, включаючи прямі способи оцінки (опитування), однак усі вони мають обмеження та особливості (як-от неповна, неточна, нерелевантна, узагальнююча інформація). Тому аналіз статистичних даних конкурсу «Молодий вчений року» за 2021—2024 рр. та прогнозування тенденцій розвитку наукових напрямків з подальшим доповненням інформаційного базису на основі якого розробляються політики укріплення наукового потенціалу України, і стало метою дослідження. Новизною роботи є окреслення перспектив використання статис тичних результатів молодіжних конкурсів на кшталт «Молодий вчений року» у формуванні інформаційного базису для системної оцінки продуктивних наукових кадрів. Визначено, що ретроспективні дослідження статистичних даних молодіжних конкурсів серед науковців можуть вдало доповнити пул даних щодо наукового потенціалу України та зменшити ризики і невизначеності в ухваленні рішень стейкхолдерами. Оцінено активність молодих науковців за галузями наук: потужний науковий потенціал встановлено за гуманітарним напрямком («Економіка», «Педагогіка», «Екологія», «Охорона навколишнього середовища»). Спрогнозовано тенденції активності наукової молоді на наступні чотири роки: дані свідчать про відносну сталість процесу розвитку науки в Україні. Наголошено на необхідності стимулювання формування наукових кадрів закладів вищої освіти (ЗВО) та наукових установ, представлених докторами наук. Підтверджено важливість публікаційної діяльності вчених як одного з оціннних індикаторів наукового потенціалу. Встановлено, що такі наукові активності як стажування та грантова діяльність потребують суттєвої підтримки. Under complex socio-economic conditions, young scientific personnel represent a key factor in maintaining the current level of economic functionality in the country and ensuring its further innovative development. Recent negative trends, including the emigration of productive forces, funding constraints, and the scientific passivity of youth, highlight the urgent need to develop mechanisms and instruments for preserving and enhancing the state’s scientific assets. However, any managerial decision, particularly those related to policies aimed at stimulating the development of scientific potential, is impossible without a thorough assessment of the actual state of affairs — namely, an analysis of both the quantitative and qualitative characteristics of the country’s scientific personnel and an evaluation of its scientific potential. Currently, there is a significant variability in approaches to such assessments, including direct evaluation methods such as surveys. However, all existing approaches have limitations and specificities (e.g., incomplete, inaccurate, irrelevant, or overly generalized information). Therefore, the analysis of statistical data from the “Young Scientist of the Year” competition for 2021—2024 and the forecasting of trends in the development of scientific disciplines, supplemented by an informational basis for policy formulation aimed at strengthening Ukraine’s scientific potential, constituted the primary objective of this study. The novelty of this research lies in outlining the prospects for utilizing statistical data from youth competitions like “Young Scientist of the Year” as a foundational element for a systematic assessment of productive scientific personnel. The study establishes that retrospective analyses of statistical data from such competitions among young scientists can significantly contribute to the dataset on Ukraine’s scientific potential, thereby reducing risks and uncertainties in decision-making by stakeholders. The study evaluates the research activity of young scientists across scientific fields, identifying a strong scientific potential in the humanities, particularly in “Economics,” “Pedagogy,” “Ecology,” and “Environmental Protection.” Based on the analyzed data, forecasts for young scientists’ activity over the next four years indicate a relative stability in the development of science in Ukraine. The findings emphasize the necessity of stimulating the formation of scientific personnel within higher education institutions and research institutions, particularly among Doctor of Science holders. Additionally, the study confirms the importance of scientific publications as a key indicator in assessing scientific potential. It is established that scientific activities such as internships and grant participation require substantial support to enhance the research capabilities of young scholars.
Study of the scientific potential of Ukraine: analytical review of the results of the «young scientist of the year» competition
Keywords: науковий потенціал; лідерські змагання; молодий вчений; економічна безпека; грантова підтримка; scientific potential; leadership competitions; young scientist; economic security; grant support